Protective Effect of Atorvastatin on Benzopyrene-Induced Hepatorenal Toxicity: A Histopathological Study - Abbasali Karimpour; Mansoureh Mirzaei; Zahra Rahmani; Amir Esmaeinejad Mogaddam; Abbas Noori; Fereshteh Talebpour Amiri (Journal of Mazandaran University of Medical Sciences, 2022)
Background and purpose: Benzo[a]pyrene (BaP) is an environmental pollutant that has genotoxic and carcinogenic effects. Atorvastatin (ATV), as a lipid-lowering drug, has antioxidant, anti-inflammatory and anti-apoptotic properties. This study investigated the effects of ATV on chronic liver and kidney damage induced by BaP. Materials and methods: In this experimental study, adult female rats were randomly divided into seven groups (n= 8 per group), including control group, olive oil group, ATV group (10 mg/kg), BaP groups (10 and 20 mg/kg), and ATV + BaP groups (10 and 20 mg). The drugs were administered by oral gavage for ten consecutive days. Histopathologic evaluation of the liver and kidney tissues was done one month after drug administration. Results: Histopathologic changes in both liver and kidney tissues such as inflammatory cell infiltration, plasma leakage, reduced acidophilia of hepatocytes, and renal tubular cells were seen in the groups receiving BaP. Findings showed that BaP at 20 mg/kg caused more serious harm than that at 10 mg/kg. ATV treatment protected structural changes in liver and kidney tissues. Conclusion: Current study showed that destructive effects of benzopyrene remain until one month after administration. The protective effects of atorvastatin against benzopyrene-induced hepatotoxicity were confirmed over time.